Evaluation of the competence and attitudes of primary care physicians towards information technology - Vogelzang, Barnabas Heinrich (Department of Human Biology, 2017)
The aim of this project was to produce some principles that would assist software developers (SD's) in the design of software for South African general medical practitioners (GP's). The author wanted to give SD's a cognitive model of general medical practice in the hope that this will improve the relevancy of future medical software. This cognitive model is in the form of a set of principles that SD's can keep in mind when developing software for GP's. An evaluation was done of the attitudes and competence of GP's towards information technology. This was done via detailed telephonic interviews, which were analyzed in order to deduce these principles.